The Influence of the Coffee Business on Farmers Income at Mentari Women Farmers Group (KWT) North Lombok - Hajat Hermawati, Nurul; Herdiana, Herdiana; Mappanganro, Nurlailah (Sharia Business Management Department of STEBIS Bina Mandiri, 2023)
Indonesia is a country that has great potential in the diversity of natural resources that can be profitable. One of the plantation products is coffee, coffee is a plantation product that has a fairly good market and business opportunities at home and abroad. the research objective was to determine the contribution of the coffee business to farmers' income at Mentari womens group in Rempek Village Ganga District. Data collection was carried out using survey techniques, namely direct interviews with respondents and guided by a list of questions that had been prepared beforehand the net income earned by the mentari farming women group is IDR 20,351,000 in one production while the average production of coffee farming in the group is 3,015 pcs per hectare at a price of 15,000. Based on the results of this study it was concluded that the production costs incurred by the mentari women farming group are IDR 24,874,000. The high cost of production is due to the cumulative result of the cost of depreciation of tools and machines used for production. The constraints faced by farmers in coffee farming are climate, environment, production and pests and diseases